If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -2y = -1x Add 'x' to each side of the equation. -1x + x + -2y = -1x + x Combine like terms: -1x + x = 0 0 + -2y = -1x + x -2y = -1x + x Combine like terms: -1x + x = 0 -2y = 0 Solving -2y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-2'. y = 0 Simplifying y = 0
| 8+x=(24-x)-(19-3x) | | 7=d-d+5 | | 7 = d2+ 5 | | 5x+1=6x+1 | | -6k-2=34 | | 9x-4x=5x-2 | | X/30=2 | | K/K^0.25 | | 3j-18=33 | | 5x-12=-52 | | 6=-3-x | | 4z-2x=18 | | udx+(1-3u)xdu=3u^2(e^3u)du | | 20-x/5=15 | | 9p+3=30 | | 42+5q=41 | | 5y-z=14 | | 12t^2-55t+90=0 | | 2x+8-7(x+1)=3x+8 | | 3.4n-9.2=-12.2+2.4n | | 7u+8=50 | | 6r+(-1)+6r=11 | | X+3x+6=0 | | 3-(2-3)= | | y-(2-y)= | | (8d-20)(8d-6)=0 | | X=0.5*(16-8y) | | (8x-20)(8d-6)=0 | | 6*x=64-2x | | 15/x-4=2/x | | 4x^2+18x=22 | | Sin(2x)tan(x)-tan(x)=0 |